AttentionHR: An Enhanced Transformer-Based Deep Learning Framework for Predicting Employee Turnover in the IT Industry - Yang, Yulan; Yang, Jinlan; Luo, Haiming (International Journal of Advanced AI Applications, 2025)
This study proposes AttentionHR, an enhanced Transformer-based deep learning model addressing the increasingly critical talent retention challenge in the IT and Internet industries. The model maps multidimensional employee data—including personal attributes, work status, and organizational environment factors—into a high-dimensional space through feature embedding techniques and incorporates an improved multi-attention mechanism to deeply analyze dynamic feature interactions. Experimental results demonstrate the model's superior performance compared to traditional machine learning methods, achieving 88.16% accuracy. Feature importance analysis reveals that salary level, job satisfaction, and technology stack updating pressure are the three most influential factors affecting IT employee turnover. In practical implementation at an Internet company, the model successfully identified 85% of actual departure cases and reduced turnover rates from 25% to 12% through timely interventions. These findings provide valuable data-driven support for IT companies to formulate targeted talent retention strategies, offering significant theoretical and practical contributions to the intelligent transformation of talent management.